Waqf Regulation: Potential and Social Problems of Mosque-Based Productive Waqf Management - Suhairi Suhairi; Khoirul Abror; Agus Alimuddin; Oki Hajiansyah Wahab (Faculty of Law, Jambi University, 2021)
Waqf land in Indonesia is very large and very wide. But there has not been a maximum productive waqf management. The management of productive waqf that can be done is mosque-based. This article attempts to study the potential and social problems of mosque-based productive waqf management. It explored mosques in the study, ranging from The Jami’ mosque of Batanghari of East Lampung Regency, Babussalam Pekalongan Mosque of East Lampung Regency, Taqwa Mosque of Punggur, Central Lampung Regency, and Al-Muhajirin Mosque Abung Semuli of North Lampung Regency. Of the four mosques studied, it can be stated that all have the potential to be carried out productive waqf management considering assets like yard and strategic location and have strategic position to build businesses centres like shops / minimarkets, BMT, food stalls, clinics, schools, fish ponds. Despite the existence of the Law on Waqf that allows the Nazhir to get not more than 10% of the profit, the waqf treasures of the mosques are not well managed by the nazhir, especially in its utilization